Relationship Between Serum Melatonin Levels and Bone Mineral Density in Postmenopausal Women with Type 2 Diabetes Mellitus. - Li, Jun; Li, Yaxin; Zhu, Yecheng; Li, Siyuan; Lu, Yunqiu; Tian, Hangning (Clinical Medicine Insights: Endocrinology & Diabetes, 2026)
Background: To investigate the association between melatonin levels and bone mineral density (BMD) in postmenopausal women with type 2 diabetes mellitus (T2DM). Methods: One hundred and ninety postmenopausal women who visited the clinic between September 2023 and September 2024 were selected and divided into 4 groups according to their disease status: the normal group (n = 45); the abnormal bone mass group (n = 43); the T2DM group (n = 46); and the T2DM with abnormal bone mass group (n = 56). Relevant glycolipid metabolism biochemical indexes, bone metabolism markers and melatonin levels were detected and statistically analyzed. Results: Comparison of melatonin levels showed that melatonin levels were significantly lower in the abnormal bone mass group, the T2DM group, and the T2DM with abnormal bone mass group [100.00 (94.00, 110.00), 99.00 (91.75, 100.25), and 92.50 (84.75, 99.00)] than in the normal group [127.71 (116.23, 137.68)], and melatonin levels were the lowest in the T2DM with abnormal bone mass group (P <.01). Melatonin levels were positively correlated with both lumbar spine L1 to L4 BMD and femoral neck BMD. T2DM differed in the role of melatonin in associating with BMD at different sites. For lumbar spine L1 to L4 BMD, the mediating effect of T2DM was not significant (percentage: −8.16%, 95% CI, −90.39 to 57.00), and for femoral neck BMD, T2DM played a significant mediating role, with its effect accounting for 33.95% (95% CI, 5.38-70.00) of the total effect. Receiver operating characteristic (ROC) curve analysis showed that the area under the curve (AUC) of the operating characteristics of subjects with melatonin levels diagnosing osteoporosis (OP) was 0.942 (95% CI, 0.902-0.982). The optimal cut-off value was 124.29 pg/mL when the Jordon index was 0.571, corresponding to a sensitivity and specificity of 57.8% and 99.3%, respectively. Multiple linear regression analysis showed that a decreased melatonin level was a risk factor for decreased BMD. Conclusion: Lower serum melatonin levels in postmenopausal women with T2DM are an independent risk factor for decreased BMD, and T2DM partially mediates the protective effect of melatonin on femoral neck BMD. Serum melatonin levels have a specific diagnostic value for abnormal bone mass in postmenopausal women with T2DM. Plain Language Summary: Relationship Between Serum Melatonin levels and Bone Mineral Density in Postmenopausal Women with Type 2 Diabetes Mellitus Why this study? The incidence of type 2 diabetes mellitus (T2DM) and osteoporosis (OP) is increasing every year, but the pathogenesis remains unclear. Melatonin is thought to be associated with T2DM and OP. Therefore, the aim of this study was to assess the association between melatonin levels and bone mineral density (BMD) in postmenopausal women with T2DM. What did the researchers do? This case-control study collected data from 190 postmenopausal women categorized into the normal group (n=45), the abnormal bone mass group (n=43), the T2DM group (n=46), and the T2DM with abnormal bone mass group (n=56). Baseline data and biochemical parameters were collected. BMD was measured using dual-energy X-ray absorptiometry, melatonin levels were determined using enzyme-linked immunosorbent assay (ELISA), and mediation analysis was performed using R-package mediation. Data were analyzed using SPSS 27.0 software. What did the researchers find? Lower serum melatonin levels in postmenopausal women with T2DM are an independent risk factor for decreased BMD, and T2DM partially mediates the protective effect of melatonin on femoral neck BMD. Serum melatonin levels have a specific diagnostic value for abnormal bone mass in postmenopausal women with T2DM. What do these findings mean? Lower levels of melatonin are strongly associated with abnormal bone metabolism in postmenopausal T2DM patients, and lower levels are an important risk factor for decreased BMD. The protective effect of melatonin on bone may be site-specific, and its positive effect on femoral neck BMD is partly mediated by modulating the pathological process of T2DM. Therefore, regular monitoring of melatonin levels in postmenopausal women with OP risk factors may help to identify early bone loss and slow its progression.